2012
DOI: 10.1068/p7085
|View full text |Cite
|
Sign up to set email alerts
|

Giving Subjects the Eye and Showing Them the Finger: Socio-Biological Cues and Saccade Generation in the Anti-Saccade Task

Abstract: Abstract. Pointing with the eyes or the finger occurs frequently in social interaction to indicate direction of attention and one's intentions. Research with a voluntary saccade task (where saccade direction is instructed by the colour of a fixation point) suggested that gaze cues automatically activate the oculomotor system, but non-biological cues, like arrows, do not. However, other work has failed to support the claim that gaze cues are special. In the current research we introduced biological and non-biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
(85 reference statements)
0
24
0
Order By: Relevance
“…Taken together, these findings suggest that gestures interact with the executive control of attention, rather than the encoding or maintenance of information. This view receives further support from studies showing that the kinds of gestures that our participants used-that is, pointing-are used to direct attention (Bangerter, 2004;Gregory & Hodgson, 2012;Tomasello, Carpenter, & Liszkowski, 2007). However, WM capacity might be the result of a complex interaction between information retention and attention control (Unsworth & Engle, 2007).…”
Section: Discussionmentioning
confidence: 73%
“…Taken together, these findings suggest that gestures interact with the executive control of attention, rather than the encoding or maintenance of information. This view receives further support from studies showing that the kinds of gestures that our participants used-that is, pointing-are used to direct attention (Bangerter, 2004;Gregory & Hodgson, 2012;Tomasello, Carpenter, & Liszkowski, 2007). However, WM capacity might be the result of a complex interaction between information retention and attention control (Unsworth & Engle, 2007).…”
Section: Discussionmentioning
confidence: 73%
“…It has been found that motions associated with animacy (suggesting self-propelled and self-directed action) capture visual attention more strongly than inanimate motions (Pratt, Radulescu, Guo, & Abrams, 2010). Moreover, in a recent study using an anti-saccade task, Gregory and Hodgson (2012) showed that a pointing hand affected saccadic reaction times, whereas a pointing arrow did not. The authors suggested that pointing fingers may influence the oculomotor system more effectively than arrows because of their biological nature.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental learning accounts of cueing effects posit that other socially salient cues can develop through development. For instance, it has been shown that finger pointing can trigger covert attention orienting, even when the hand‐cue is completely nonpredictive of target location (Ariga & Watanabe, ; Gregory & Hodgson, ; Tomonaga & Imura, ; see also, Daum, Ulber, & Gredebäck, ). In fact, a recent study on 137 hearing children (aged 3–10 years old) found stronger effects of hand pointing compared to eye gaze cueing across all age ranges (Gregory et al, ).…”
Section: Discussionmentioning
confidence: 99%